Digitalization and development of a torque sensor based control system and implementation of the algorithm using a micro-controller - Shantonu, Omar Shahjalal; Shafiq, Afia Abeeda; Hassan, Raziul; Ahmed, Md. Safayet (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.